2019
DOI: 10.1507/endocrj.ej18-0191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a diet with or without physical activity on angiopoietin-like protein 8 concentrations in overweight/obese patients with newly diagnosed type 2 diabetes: a randomized controlled trial

Abstract: Angiopoietin-like protein 8 (ANGPTL8) is a newly discovered adipokine plays an important role in energy homoeostasis, obesity and type 2 diabetes (T2D). Although lifestyle modification in obesity and T2D is known to offer metabolic benefits, there is paucity of comprehensive data on change in ANGPTL8. We investigated the effect of lifestyle intervention on ANGPTL8 concentrations. 384 obese/overweight adults with newly diagnosed T2D were randomly assigned (1:1:1) to diet (n = 128), diet + activity (n = 128) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Some studies have explored the effect of weight change on betatrophin, presenting with inconsistent results. A study reported that serum betatrophin levels decrease after diet-related weight loss [16] while another noted that only surgeryinduced weight loss increases blood betatrophin levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have explored the effect of weight change on betatrophin, presenting with inconsistent results. A study reported that serum betatrophin levels decrease after diet-related weight loss [16] while another noted that only surgeryinduced weight loss increases blood betatrophin levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have explored the effect of weight change on betatrophin, presenting with inconsistent results. A study reported that serum betatrophin levels decrease after diet-related weight loss [16] while another noted that only surgery-induced weight loss increases blood betatrophin levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have explored the effect of weight change on betatrophin, presenting with inconsistent results. A study reported that serum betatrophin levels decrease after diet-related weight loss [16] while another noted that only surgery-induced weight loss increases blood betatrophin levels [17].…”
Section: Introductionmentioning
confidence: 99%